COMPARATIVE STUDY OF SOME FLC-BASED MPPT METHODS FOR PHOTOVOLTAIC SYSTEMS - Al Gizi, Ammar; Al Chlaihawi, Sarab; Craciunescu, Aurelian (MATTER: International Journal of Science and Technology, 2017)
In this paper, an asymmetrical and symmetrical fuzzy logic controller (FLC) based maximum power point tracking (MPPT) methods are compared. The input membership function (MF) setting values are calculated based on the power-voltage (P-V) characteristics of the utilized photovoltaic (PV) module at standard technical conditions (STC). Moreover, five and seven triangular (5-tri and 7-tri) MFs are analyzed. The performance comparisons of the different categories of the FLC-based PV MPPT methods are performed using Matlab/Simulink package. A BP SX150S PV module is used in the simulation at STC. According to the simulation results, the asymmetrical FLC-based MPPT method has the superior results in terms of transient and steady state tracking performances for the different numbers of MFs. In the case of 5-tri MFs, the asymmetrical FLC-based MPPT method can enhance the rising time (tr), tracking accuracy, and energy yield by 84%, 0.05%, and 13.25% respectively, compared to the symmetrical FLC. Whereas, in the case of 7-tri MFs, the rising time, tracking accuracy, and extracted energy are enhanced by 86.7%, 0.04%, and 14.72% respectively. The rising time and extracted energy are improved approximately by 10% and 0.08%, respectively, by using 7-tri MFs in the asymmetrical FLC. Consequently and regardless of the number of MFs, the asymmetrical FLC can be used as the most promising MPPT method for improving the overall performance of the PV system.